Social norms and religious values in the context of public expenditure law (on the example of the Polish society) - Szafranek, Anna; Tyniewcki, Marcin (Prawo Kanoniczne, 2021)
Results of many polls show that a significant part of the Polish society identifies with the dogma of Catholicism, which suggests that their everyday life should comply with the dogma. As a result, Poland is a suitable research area to analyse the relation between ethical norms, religious values and Polish public expenditure law yet it must be stated that the matter is universal. The topic of the aforementioned relation will be the subject of this article. Furthermore, authors aimed to verify a thesis that the meaning of moral norms and their perception differs depending on whether it is analysed on the micro (individual perception, as a part of small social groups, for example, family), mezzo (local community) or macro (Polish society in general) scale. The article concludes with findings from the conducted analysis in the context of public expenditure law-making.